(untitled) (Third Sector Social Economic Review, 2026)
This study analyzes the mass protests that emerged in Iran following the death of Mahsa Amini in 2022 within the framework of feminist theory and social movement studies. The primary aim of the article is to question whether these protests should be conceptualized as a “feminist revolution” or rather as a contemporary manifestation of historically accumulated feminist resistance. In this regard, the article approaches the Iranian protests not as isolated or reactive political events, but as part of a long-term process shaped by historical continuity and collective feminist memory. The research adopts a qualitative methodology based on historical-discursive analysis and documentary review. Academic literature, secondary historical sources, and international media reports and human rights documents related to the 2022 protests constitute the main data set. Feminist theory, social movement theory, and the intersectionality approach are employed as key analytical tools. The findings indicate that although the protests did not result in immediate regime change, they contributed to a significant erosion of normative compliance by exposing the political control mechanisms imposed on women’s bodies in the public sphere. The slogan “Woman, Life, Freedom” is interpreted as the symbolic and discursive condensation of accumulated feminist resistance. The study concludes that the Iranian protests should be understood not as a revolutionary rupture, but as a multi-layered and intersectional expression of feminist accumulation, offering a theoretical contribution to the analysis of women’s movements under authoritarian regimes. The research adopts a qualitative methodology based on historical-discursive analysis and documentary review. Academic literature, secondary historical sources, and international media reports and human rights documents related to the 2022 protests constitute the main data set. Feminist theory, social movement theory, and the intersectionality approach are employed as key analytical tools. The findings indicate that although the protests did not result in immediate regime change, they contributed to a significant erosion of normative compliance by exposing the political control mechanisms imposed on women’s bodies in the public sphere. The slogan “Woman, Life, Freedom” is interpreted as the symbolic and discursive condensation of accumulated feminist resistance. The study concludes that the Iranian protests should be understood not as a revolutionary rupture, but as a multi-layered and intersectional expression of feminist accumulation, offering a theoretical contribution to the analysis of women’s movements under authoritarian regimes.